The role of growth, energy, and resource utilization in ecological footprints: navigating BRICS + environmental challenges - Riaz, Mahmud Hasan; Alam, Montasir; Ali, Ayub; Ahmed, Zobayer; Raihan, Asif (Letters in spatial and resource sciences, 2025)
This study investigates the impact of natural resource exploitation, renewable energy consumption, economic growth, biocapacity, and information and communication technologies (ICT) on the ecological footprint of BRICS + nations (Brazil, Russia, India, China, South Africa, and newly joined Argentina, Egypt, Ethiopia, Iran, Saudi Arabia, and UAE) from 1991 to 2019. Using advanced econometric techniques, including FMOLS, DOLS, CCR, and GMM, the findings reveal that natural resource exploitation and economic growth exacerbate ecological degradation, whereas renewable energy and biocapacity reduce environmental pressures. ICT’s impact remains statistically insignificant in the current context. The study emphasizes the need for BRICS + nations to adopt tailored policy frameworks integrating renewable energy, promoting sustainable resource use, and enhancing biocapacity to achieve Sustainable Development Goals (SDGs) 7, 12, and 13. The research offers critical insights for balancing economic growth with environmental sustainability in diverse and rapidly industrializing economies.